Defects and Doping in Nanocrystalline Silicon-Germanium Devices. Issue 1666 (19th August 2014) - Konduri, Siva; Mulder, Watson; Dalal, Vikram L.
ABSTRACT: Nanocrystalline Silicon-Germanium (Si, Ge) is a potentially useful material for photovoltaic devices and photo-detectors. Its bandgap can be controlled across the entire bandgap region from that of Si to that of Ge by changing the alloy composition during growth. In this work, we study the fabrication and electronic properties of nanocrystalline devices grown using PECVD techniques. We discovered that upon adding Ge to Si during growth, the intrinsic layer changes from n-type to p-type. We can change it back to n-type by using ppm levels of phosphorus, and make reasonable quality devices when phosphine gas was added to the deposition mix. We also measured the defect density spectrum using capacitance frequency techniques, and find that defect density decreases systematically as more phosphine is added to the gas phase. We also find that the ratio of Germanium to Silicon in the solid phase is higher than the ratio in the gas phase.